Desenhando através da luz - experiências de prazer em ambientes comerciais - Tonelotto, Simone Rendwanski (Universidade do Vale do Rio dos Sinos, 2013)
The challenge for this study is investigate how design can build pleasure experiences beyond the lighting in commercial spaces. For this the Research is not focused in the physiological effects of lighting, already known, but make a approach of how the lighting can contribute in emotions of the user of space. The study of pleasure beyond lighting presents a new conversation in the experience field in the point of purchase and identifies the potential of a space as a projetual increment. For this a exploratory study associated with in-depth interviews with lighting designers show a rich sampling how designers deal with this factors on projects, verifying in the practice the relevance of the designer’s expertise in the resolution of project issues and in the knowledge given the lack of research, come forward other areas.
Keywords: Projeto; Experiência; Emoção; Prazer; Ambiente comercial; Iluminação; Project; Experience; Emotion; Pleasure; Retail and lighting design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial